Improving Security and Privacy in Decentralized Cloud Storage - Nagamani Gonthina, C.Jagadeeswari, Keerthi Sai Bheemavarapu and Sharanya Arpally (International Journal of Advanced Science and Technology, 2020)
In the current generation Cloud computing is the major utility being used by multiple organizations to meet the governance of their data and resource management. The amenities of cloud are provided by various third party service providers, whom cannot be trusted completely. So security becomes the crucial point with various data providers in the market. The proposed scheme allows the data to be stored and resources to be managed securely by minimizing the computational costs. This model aims at distributed cloud services for storage with All-Or-Nothing-Transform for effective resource conservation. Furthermore, a unidirectional proxy re-encryption (UPRE) scheme is employed to minimize the inflated computational costs along with numerous data providers. Our proposed model empowers organization owners to manage their environment by providing security with minimized computational costs.